2018
DOI: 10.1136/bmj.k1343
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex of surgeons and mortality of older surgical patients: observational study

Abstract: ObjectiveTo investigate whether patients’ mortality differs according to the age and sex of surgeons.DesignObservational study.SettingUS acute care hospitals.Participants100% of Medicare fee-for-service beneficiaries aged 65-99 years who underwent one of 20 major non-elective surgeries between 2011 and 2014.Main outcome measureOperative mortality rate of patients, defined as death during hospital admission or within 30 days of the operative procedure, after adjustment for patients’ and surgeons’ characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
88
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 51 publications
(86 reference statements)
7
88
3
Order By: Relevance
“…Our work is consistent with the findings of previous studies that showed better performance by older surgeons, 16 but we studied both elective and emergent operative procedures over a much wider patient age range than previously studied. Furthermore, we have shown consistency in results by using additional indicators of surgical outcomes beyond mortality alone (i.e., readmission and complications).…”
Section: Discussionsupporting
confidence: 91%
“…Our work is consistent with the findings of previous studies that showed better performance by older surgeons, 16 but we studied both elective and emergent operative procedures over a much wider patient age range than previously studied. Furthermore, we have shown consistency in results by using additional indicators of surgical outcomes beyond mortality alone (i.e., readmission and complications).…”
Section: Discussionsupporting
confidence: 91%
“…These findings conflict with previous studies of hospital physicians in the US and surgeons in Canada, both of which showed superior adjusted outcomes among patients treated by female clinicians 25. Taken together, however, these studies are important 125. In 2018 discrimination based on age, race, gender, and sexual orientation persists, albeit in more insidious forms—subtle innuendos, lack of respect, patients and staff assuming women are not surgeons or surgical decision makers, referral biases, and undermining “locker room talk”.…”
contrasting
confidence: 91%
“…Tsugawa and colleagues found no association between surgeons’ sex and patients’ outcomes, although patients treated by female surgeons aged 50-59 had the lowest overall mortality 1. These findings conflict with previous studies of hospital physicians in the US and surgeons in Canada, both of which showed superior adjusted outcomes among patients treated by female clinicians 25.…”
mentioning
confidence: 85%
See 2 more Smart Citations